Alleles of a wall‐associated kinase gene account for three of the major northern corn leaf blight resistance loci in maize. (24th March 2021) - Yang, Ping; Scheuermann, Daniela; Kessel, Bettina; Koller, Teresa; Greenwood, Julian R.; Hurni, Severine; Herren, Gerhard; Zhou, Shenghui; Marande, William; Wicker, Thomas; Krattinger, Simon G.; Ouzunova, Milena; et al.
SUMMARY: Northern corn leaf blight, caused by the fungal pathogen Setosphaeria turcica (anamorph Exserohilum turcicum ), is one of the most devastating foliar diseases of maize ( Zea mays ). Four genes Ht1, Ht2, Ht3 and Htn1 represent the major sources of genetic resistance against the hemibiotrophic fungus S. turcica . Differential maize lines containing these genes also form the basis to classify S. turcica races. Here, we show that Ht2 and Ht3 are identical and allelic to the previously cloned Htn1 gene. Using a map‐based cloning approach and Targeting Induced Local Lesions in Genomes (TILLING), we demonstrate that Ht2/Ht3 is an allele of the wall‐associated receptor‐like kinase gene ZmWAK‐RLK1 . The ZmWAK‐RLK1 variants encoded by Htn1 and Ht2/Ht3 differ by multiple amino acid polymorphisms that particularly affect the putative extracellular domain. A diversity analysis in maize revealed the presence of dozens of ZmWAK‐RLK1 alleles. Ht2, Ht3 and Htn1 have been described over decades as independent resistance loci with different race spectra and resistance responses. Our work demonstrates that these three genes are allelic, which has major implications for northern corn leaf blight resistance breeding and nomenclature of S. turcica pathotypes. We hypothesize that genetic background effects have confounded the classical description of these disease resistance genes in the past. Significance Statement: Northern corn leaf blight is one of the most devastating foliar diseases of maize. We prove that resistance genes Ht2 and Ht3 are identical and allelic to another gene Htn1, which encodes ZmWAK‐RLK1 . Ht2, Ht3 and Htn1 have been described over decades as independent resistance loci with different race spectra and resistance responses. Our work demonstrates that these three genes are allelic, which has major implications for northern corn leaf blight resistance breeding and nomenclature of Setosphaeria turcica pathotypes.